Extreme changes in the equatorial electrojet under the influence of interplanetary electric field and the associated modification in the low-latitude F region plasma distribution - Simi, K.G.; Thampi, Smitha V.; Chakrabarty, D.; Pathan, B.M.; Nayar, S. R. Prabhakaran; Pant, Tarun Kumar (My University, 2012)
A case of the drastic effects of an eastward prompt penetration and a westward overshielding electric field successively affecting the daytime equatorial ionosphere during the space weather event that occurred on 24 November 2001 is presented. Under the influence of the strong eastward prompt penetration electric field starting from 11:25 Indian standard time (IST), the equatorial electrojet (EEJ) strength reached the maximum value of 225 nT at 12:42 IST, almost 7 times greater than the monthly quiet time mean at the same time. This peak EEJ value exceeds the maximum observed values during the month of November for the entire solar cycle by more than 100 nT, irrespective of quiet or disturbed conditions. Further, owing to an ensuing overshielding event that occurred during the main phase of the storm rather than the end of the main phase, this unusually large EEJ showed an equally strong polarity reversal along with a weakening of the sporadic E layer over the equator. The EEJ strength was reduced from +225 to −120 nT at ∼13:45 IST, resulting in a strong counter electrojet condition. The latitudinal variation of the F region electron density data from the CHAMP satellite reveal an ill-developed equatorial ionization anomaly at 17:00 IST (11:24 UT) over the Indian sector due to this significant weakening of the zonal electric field. These observations showcase the significant degree to which the low-latitude ionosphere can be affected by the interplanetary electric field.
Keywords: Equatorial electrojet; Interplanetary electric field; CHAMP satellite